Two Infants With Beta-Ketothiolase Deficiency Identified by Newborn Screening in China - Yang, Yuqi; Jiang, Shu hong; Liu, Shuang; Han, Xiao ya; Wang, Ying; Wang, Lei lei; Yu, Bin (Frontiers in Genetics, 2019)
Beta-ketothiolase deficiency (BKTD) is an autosomal recessive disease caused by a defect of mitochondrial acetoacetyl-CoA thiolase. Beginning in 2014, we carried out newborn screening by tandem mass spectrometry MS/MS followed by next-generation sequencing (NGS) and identified two infants with BKTD from among 203,750 newborns born in Jiangsu Province, China. Both infants showed the characteristic chemical abnormalities of BKTD. We used NGS to confirm variants in the ACAT1. Patient 1 had the compound heterozygous variants c.721dupA and c.928G>C. Patient 2 had compound heterozygosity for the c.238+1G>A and c.1163G>T variants. c.721dupA, c.928G>C and c.1163G>T were suspected to be likely pathogenic, whereas c.238+1G>A was determined to be pathogenic. None of the four variants have been reported in the literature. Patient 1 presented with onset of metabolic acidosis and neonatal hypoglycemia 8 days after birth, whereas patient 2 was detected through neonatal disease screening but had no clinical manifestations. These findings contribute to our understanding of the clinical characteristics and genetic basis of BKTD.